Mitochondrial plasticity supports proliferative outgrowth and invasion of ovarian cancer spheroids during adhesion - Grieco, Joseph P.; Compton, Stephanie L. E.; Bano, Nazia; Brookover, Lucy; Nichenko, Anna S.; Drake, Joshua C.; Schmelz, Eva M. (Frontiers in Oncology, 2023)
Background Ovarian cancer cells aggregate during or after exfoliation from the primary tumor to form threedimensional spheroids. Spheroid formation provides a survival advantage during peritoneal dissemination in nutrient and oxygen-depleted conditions which is accompanied by a suppressed metabolic phenotype and fragmented mitochondria. Upon arrival to their metastatic sites, spheroids adhere to peritoneal organs and transition to a more epithelial phenotype to support outgrowth and invasion. In this study, we investigated the plasticity of mitochondrial morphology, dynamics, and function upon adhesion. Methods Using our slow-developing (MOSE-L) and fast-developing (MOSE-LTICv) ovarian cancer models, we mimicked adhesion and reoxygenation conditions by plating the spheroids onto tissue culture dishes and changing culture conditions from hypoxia and low glucose to normoxia with high glucose levels after adhesion. We used Western Blot, microscopy and Seahorse analyses to determine the plasticity of mitochondrial morphology and functions upon adhesion, and the impact on proliferation and invasion capacities. Results Independent of culture conditions, all spheroids adhered to and began to grow onto the culture plates. While the bulk of the spheroid was unresponsive, the mitochondrial morphology in the outgrowing cells was indistinguishable from cells growing in monolayers, indicating that mitochondrial fragmentation in spheroids was indeed reversible. This was accompanied by an increase in regulators of mitobiogenesis, PGC1a, mitochondrial mass, and respiration. Reoxygenation increased migration and invasion in both cell types but only the MOSE-L responded with increased proliferation to reoxygenation. The highly aggressive phenotype of the MOSE-LTICv was characterized by a relative independence of oxygen and the preservation of higher levels of proliferation, migration and invasion even in limiting culture conditions but a higher reliance on mitophagy. Further, the outgrowth in these aggressive cells relies mostly on proliferation while the MOSE-L cells both utilize proliferation and migration to achieve outgrowth. Suppression of proliferation with cycloheximide impeded aggregation, reduced outgrowth and invasion via repression of MMP2 expression and the flattening of the spheroids. Discussion Our studies indicate that the fragmentation of the mitochondria is reversible upon adhesion. The identification of regulatory signaling molecules and pathways of these key phenotypic alterations that occur during primary adhesion and invasion is critical for the identification of druggable targets for therapeutic intervention to prevent aggressive metastatic disease.